The perception of fairness in infant care and mothers' postpartum depression. (October 2017) - DeMaris, Alfred; Mahoney, Annette
Abstract: This study investigates a potential causal effect of mothers' perceptions of the fairness of infant care on their postpartum depression. Based on the tenets of equity theory, it is hypothesized that, net of controls, mothers who see infant care as fairly apportioned between themselves and their husbands will be less depressed than others. We utilize data from a longitudinal study of a nonrandom sample of 178 heterosexual couples experiencing the birth of their first child together. The primary focus variable is the mothers' perception in the first couple of months postpartum that infant care is fair to them. Statistical analysis involved the careful chronological sequencing of response variable and controls, along with regression modeling using propensity scores. We find that a perception of fairness is associated with about a quarter of a standard deviation lower depressive symptomatology, controlling for key covariates. Depressive symptomatology is additionally elevated for mothers experiencing more pre-partum depression, and for those who more generally felt, before the birth, that they were overbenefiting in the marriage. This paper contributes to both equity theory and research on postpartum depression. In a scenario in which it is not practical or ethical to randomly assign people to fairness-in-infant-care conditions, we are able to utilize longitudinal data and a natural "experiment, " along with propensity-score modeling to attempt to assess the causal impact of fairness in infant care on postpartum depression. The finding that fairness in this arena appears to reduce postpartum depression emphasizes the importance of encouraging father participation in this critical stage of parenting. Limitations of the study with respect to causal inference are also discussed. Highlights: Equity theory says depression should be lower when childcare is perceived as fair. We compared postpartum depression for mothers in "fair" vs. "unfair" groups. We used longitudinal data and propensity-score analysis to mimic random assignment. Net of controls, infant-care fairness was related to significantly lower depression. The effect of fairness perceptions in reducing depression may well be causal.